Effects of water stress on germination of yarrow populations (Achilleaspp.) from different bioclimatic zones in Iran - Shanjani, Parvin Salehi; Izadpanah, Masoumeh; Mohamadpour, Mohamad Reza (Plant Breeding and Seed Science, 2013)
The effects of water potential on germination were studied in 18 wild populations of three yarrow species (Achillea tenuifolia, A. vermicularis and A. filipendulina) from different bioclimatic zones in Iran. Water potential between 0 and -0.6 MPa were obtained using polyethylene glycol 6000 (PEG-6000) solutions. The study of water stress on germination showed that, regardless of the species and the populations, the lowering of the water potential reduced the capacity for germination and early seeding growth. These results indicated a strong genetic potential for drought tolerance during germination within each species. These differences in germination ability of wild populations of each species might be attributed to intraspecific variations resulting from the effects of natural selection and genetic pool background.